Development of a packed bed reactor for the removal of aromatic hydrocarbons from soil using laccase/mediator feeding system - Vipotnik, Ziva (2021)
Polyaromatic hydrocarbons (PAH) are persistent pollutants of great concern due to their potential toxicity, mutagenicity and carcinogenicity. A biotechnological approach to remove PAH from soil was evaluated in this work using a laccase mediator system. Initially, laccase was produced by fungal co-cultivation, using kiwi peels as substrate. The produced laccase was applied to PAH contaminated soil to evaluate its efficiency on enzymatic bioremediation. Results showed that laccase mediator system was effective in the degradation of pyrene, fluorene, chrysene and a lower extension anthracene. Mediators improved the PAH degradation and natural mediators (ferulic acid and p-coumaric acid) were as effective as the synthetic mediator ABTS. However, the process was not effective in the benzo[a]pyrene degradation, one of the most recalcitrant and toxic PAH. This low degradation rate could be related to the low activity of the laccase mediator system in an environment lacking water. To overcome this issue, a PAH contaminated soil degradation system was developed in packed bed reactor (PBR) fed with laccase/mediator. Continuous flow of laccase/mediator improved the PAH degradation, achieving 74.8 %, 71.9 %, 72.2 %, 81.8 % and 100 % degradation for fluorene, anthracene, phenanthrene, chrysene and pyrene, respectively. This system was able to degrade 96 % benzo[a]pyrene, which was 90 % higher than the degradation in batch system. Results indicated that the produced laccase as well as the fed-batch degradation system developed in PBR could be successfully applied to the degradation of soil PAH pollutants, with the advantage of achieving higher degradation rates than in simple batch, as well as being a faster and simpler process than microorganism bioremediation.